Egr2 overexpression in Schwann cells increases myelination frequency in vitro. Issue 11 (November 2018) - Tammia, Markus; Mi, Ruifa; Sluch, Valentin M.; Zhu, Allen; Chung, Tiffany; Shinn, Daniel; Zack, Donald J.; Höke, Ahmet; Mao, Hai-Quan
Abstract: Schwann cells are key players in peripheral nerve regeneration, and are uniquely capable of remyelinating axons in this context. Schwann cells orchestrate this process via a set of transcription factors. While it has been shown that overexpression of specific genes, e.g. Egr2, upregulates myelin-related transcripts, it remains unknown if such manipulation can functionalize the cells and enhance their myelination frequency. The ability to do so could have implications in the use of human stem cell-derived Schwann cells, where myelination is hard to achieve. After screening four candidate transcription factors ( Sox10, Oct6, Brn2 and Egr2 ), we found that overexpression of Egr2 in rat Schwann cells co-cultured with sensory neurons enhanced myelination frequency and reduced cell proliferation. However, in a mouse model of sciatic nerve repair with cells engrafted within a nerve guide, myelination frequency in the engrafted cells was reduced upon Egr2 overexpression. Our results show that while overexpression of Egr2 can enhance the myelination frequency in vitro, it is context-dependent, potentially influenced by the microenvironment, timing of association with axons, expression level, species differences, or other factors.